Avaliação da adesão ao tratamento medicamentoso de pacientes hipertensos idosos em seguimento clínico ambulatorial - Lins, Allana Karen Dias (2018)
Introduction: Low compliance with drug treatment is described in elderly hypertensive patients, increasing the rate of cardiovascular complications. Improving adherence to pharmacotherapy is a preponderant factor for the reduction of morbidity and mortality and an increase in life expectancy. Objective: To evaluate the adherence to drug therapy in elderly hypertensive patients, identifying the main barriers to treatment not being performed in the way it was prescribed. Methods: A cross-sectional and descriptive epidemiological study was carried out between January and July 2018. A structured questionnaire validated and adapted to the Portuguese Brief Medication Questionnaire (BMQ) was used in hypertensive patients aged ≥ 65 years in the city of Aracaju, Sergipe, Brazil, in a Basic Health Unit (UBS) and in a Specialized Center (IPESAÚDE). Results: The study consisted of 80 individuals, of these 43 from UBS and 37 from the specialized center (IPESAUDE). The prevalent gender was female (67.5%), 37.5% of the sample were white, 48.8% were married and 96.3% were retired. According to the BMQ, 45% of the patients showed a probable adhesion and 45% likely low adhesion, 7.5% low adhesion and 2.5% adherence to the treatment. Conclusion: Although drug treatment is of high efficiency, non-compliance is the main barrier to inadequate control of hypertension. Several factors can be related, among them: advanced age, the use of polypharmacy, presence of multiple comorbidities and low socioeconomic levels.